APPLYING FUZZY TECHNOLOGY FOR DEALING WITH UNCER-TAINTY UNDER COST-BENEFIT ANALYSIS PARADIGM - Zahvoyska , Lyudmyla (Forestry, Forest, Paper and Woodworking Industry, 2024)
Traditional approaches to economic analysis of public projects could hardly deal with the vagueness and data inaccuracy arising from ex ante estimations of costs and benefits, from fuzzy language valuations so common in non-market benefits and costs appraisals, from uncertainty of economic and social processes. The fuzzy technology enables analysts to deal with these challenges. The paper presents an example of fuzzy technology application to CBA analysis of public project aimed to develop the Recovery center taking into account social and environmental values.